PENGARUH PERCEIVED ORGANIZATIONAL SUPPORT, PROACTIVE COPINGDAN WORK-LIFE BALANCETERHADAP PERCEIVED PRODUCTIVITYMELALUI BURNOUT - Evelyn, Evelyn; Anindita, Rina; Johanes, Johanes (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2024)
This study aims to determine the health impacts caused by child marriage in the North Surabaya Region of East Java Province. The identified and analyzed impacts include physical, mental, and social impacts. Marriage is crucial for every human being since it creates a balance in a person's life socially, biologically, and psychologically. This study's method used the descriptive qualitative method. Interviews and documentation are used as data collection techniques. Furthermore, the data analysis stages included the process of data reduction, data presentation, and drawing conclusions. The study’s results showed that respondents experienced physical impacts. Meanwhile, the impacts of child marriage on mental health included the husband and wife's unstable emotions and wives who tend to be passive, insecure, and afraid to make any decisions. In addition, this study showed that child marriage also made some respondents unable to be independent; instead, they depended on their husbands. The impact of social health in this study was the emergence of financial problems. Due to the children's immature age and low education level, the couples from child marriage struggle to get a decent job, resulting in they have a low income.